Smart Energy Meter Using Android Application And Gsm Network (International Journal of Engineering and Computer Science, 2017)
This is implemented for the purpose of getting a fully automized electricity billing system. This is aim  to measure and monitor the electricty consumed  by  consumers in a locality and transmitting the consumed power to the station as well as issuing the bill of consumed power automatically. It is also aims to find the malpractices in the meter.  Using this system the Electricity Board can access  all  data  regarding the consumed power in each home and in each station whenever required. From the data the Board can find out power theft also it is also offers a  system  to charge extra payment for the excess usage of power at peak time (6.00---10.00pm) .Online payment is also possible for  our  new system. GSM is using for automating the system. The consumed unit   transmission, alerts and bill reception are achieved by the GSM module in the client side as set by the user. Server station is also served by a GSM module for  transmission  and reception of data .